FLORISTIC DIVERSITY OF LOMAS DE LÚCUMO, LIMA, PERÚ - Madrid-Ibarra, Flor de María (2020)
The floristic diversity of Lomas de Lúcumo is located at UTM 18 L. 295676 East - 8649730 South in the District of Pachacamac, Province of Lima, Department of Lima, Peru, with an area of 150 ha and an elevation between 100 and 500 msnm. The Altitudinal transect method and Rapid Ecological Evaluation (EER) of the present biodiversity were used to collect information of the wild fl ora, represented with a total of 118 species distributed in 102 genera and 49 families. The families with the greatest diversity were Asteraceae and Solanaceae with 15 and 9 species, respectively. The predominant vegetation is herbaceous registered with 23 endemic species and fi ve species in conservation status and their registry will serve as a source of identity for residents, tourists, and the whole ecosystem.